2014
DOI: 10.1007/s00467-014-2933-1
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab in neonatal hemolytic uremic syndrome with homozygous factor H deficiency

Abstract: We report on the long-term efficacy and safety of eculizumab as first-line therapy in neonatal aHUS. However its use still requires optimization in terms of indications and administration (frequency, dosage).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Few case reports and series have also demonstrated long-term efficacy and safety of Eculizumab as first line treatment in neonates and infants who suffered from aHUS. Similar to our patient, neonates and infants in the studies also showed complete recovery of the renal function after initiation of Ezulizumab [16, 17]. …”
Section: Discussionsupporting
confidence: 86%
“…Few case reports and series have also demonstrated long-term efficacy and safety of Eculizumab as first line treatment in neonates and infants who suffered from aHUS. Similar to our patient, neonates and infants in the studies also showed complete recovery of the renal function after initiation of Ezulizumab [16, 17]. …”
Section: Discussionsupporting
confidence: 86%
“…This new drug was reported to be safe and effective in children in several case reports and clinical trials [20-23]. In a prospective study reported by Greenbaum et al [24], 64% of 22 pediatric patients achieved complete remission after 26 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…That eculizumab may be efficacious to rescue central nervous system involvement is suggested by nine case reports, including four in children [87,90,110,[123][124][125][126][127]. Eculizumab also appeared lifesaving in four children with myocardial involvement [83,90,92,110]. The reports of four children who developed cerebral ischemic events due to stenosis of cerebral arteries after several years on dialysis have suggested that local complement activation added to the vascular consequences of long-term dialysis may lead to such macrovascular complications [101,[128][129][130].…”
Section: Education Information Cardmentioning
confidence: 92%